2019
DOI: 10.1101/533422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA double-strand breaks induced by reactive oxygen species promote DNA polymerase IV activity inEscherichia coli

Abstract: Under many conditions the killing of bacterial cells by antibiotics is potentiated by DNA damage induced by reactive oxygen species (ROS)1–3. A primary cause of ROS-induced cell death is the accumulation of DNA double-strand breaks (DSBs)1,4–6. DNA polymerase IV (pol IV), an error-prone DNA polymerase produced at elevated levels in cells experiencing DNA damage, has been implicated both in ROS-dependent killing and in DSBR7–15. Here, we show using single-molecule fluorescence microscopy that ROS-induced DSBs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The dnaX-mKate2 allele encodes for a fluorescent fusion of the τ clamp loader protein, serving as a marker for the replisome, τ-mKate2. We previously showed that the fluorescent protein fusion of DinB-YPet is fully functional, yielding pol IV-dependent mutagenesis activity upon ciprofloxacin treatment in both dnaX + and dnaX-mKate2 cells (Henrikus et al ., 2018b; Henrikus et al ., 2019b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dnaX-mKate2 allele encodes for a fluorescent fusion of the τ clamp loader protein, serving as a marker for the replisome, τ-mKate2. We previously showed that the fluorescent protein fusion of DinB-YPet is fully functional, yielding pol IV-dependent mutagenesis activity upon ciprofloxacin treatment in both dnaX + and dnaX-mKate2 cells (Henrikus et al ., 2018b; Henrikus et al ., 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…Ciprofloxacin is a DNA gyrase inhibitor, which generates DSBs (Zhao et al ., 1997) and rapidly halts DNA synthesis (Deitz et al ., 1966; Snyder and Drlica, 1979). Defects in DSB processing strongly suppress both pol IV up-regulation and focus formation (Henrikus et al ., 2019b). Interestingly, in vitro , pol IV is capable of associating with RecA(E38K)-ATPγS filaments formed on dsDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much debate has resulted over 14 the relative contribution of these two mechanisms to the observed genomic GC 15 content in prokaryotes [8,9,5,4,7,10]. 16 This debate between proponents of the selection and BGC hypotheses con-17 tinues, with many studies focusing on patterns of genetic diversity that by them- 18 selves cannot easily differentiate between these two hypotheses because recom- 19 bination will also locally increase the efficiency of selection [11,9]; however, 20 the addition of phenotypic information provides the tantalizing clue that GC 21 content correlates with shared environmental factors [2,3,12,13] independent 22 of phylogenetic similarity [3]. Thus, these environmental factors must either 23 lead to an unknown selective advantage for high/low GC content [11] or lead to 24 elevated rates of BGC through an as-yet unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…25 We noticed that many environments containing high GC content microbes, 26 such as soils and aerobic environments [3,12], induce relatively high rates of 27 DNA damage in the form of double-strand breaks (DSB) that necessitate repair 28 [14,15]. For instance, in aerobes, this damage typically results from reactive 29 oxygen species produced during metabolism [14] that can lead to DSBs by pro- 30 ducing collapsed replication forks [16], as well as via a number of other mecha-31 nisms (often in conjunction with other stressors; [17,18,19,20,21,22,23,24]). 32 In soil-dwelling microbes, DSBs are associated with desiccation and spore for- 33 mation [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%